The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/geront/45.suppl_1.37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Life of Long-Term Care Residents With Dementia

Abstract: Various measures and sources of data provide different perspectives on quality of life. No "gold standard" exists; so a combination of methods and sources is likely to provide the most complete picture of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 30 publications
9
145
2
2
Order By: Relevance
“…Although there are nine studies did not find any relationship between demographic characteristics and QoL (Andersen et al, 2004;Grske et al, 2014;Moyle et al, 2015;Monteiro et al, 2014;Sloane et al, 2005;Winzelberg et al, 2005;Wetzels et al, 2010;Salvador et al, 2000), other studies found that higher education (Marventano et al, 2015;Li et al, 2012), males (Woods et al, 2014;Barca et al 2011), white (Black et al, 2012), widowed (Samus et al, 2005) and extroverted characteristic (Li et al, 2012) tended to be positively associated with better QoL for elderly people with dementia. Moreover, Banerjee et al (2005) found that QoL of people with dementia showed decline as with the increasing age, while Mjørud et al (2014) indicated that the QoL was worse among the youngest (<79) and oldest (>90) people with dementia.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are nine studies did not find any relationship between demographic characteristics and QoL (Andersen et al, 2004;Grske et al, 2014;Moyle et al, 2015;Monteiro et al, 2014;Sloane et al, 2005;Winzelberg et al, 2005;Wetzels et al, 2010;Salvador et al, 2000), other studies found that higher education (Marventano et al, 2015;Li et al, 2012), males (Woods et al, 2014;Barca et al 2011), white (Black et al, 2012), widowed (Samus et al, 2005) and extroverted characteristic (Li et al, 2012) tended to be positively associated with better QoL for elderly people with dementia. Moreover, Banerjee et al (2005) found that QoL of people with dementia showed decline as with the increasing age, while Mjørud et al (2014) indicated that the QoL was worse among the youngest (<79) and oldest (>90) people with dementia.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…15 studies (León-Salas et al, 2015;Garre-Olmo et al, 2012;Hodgson 19 et al, 2014;Salvador et al, 2000;Black et al, 2012;Beerens et al, 2014;Beer et al, 2010;Samus et al, 2005;Sloane et al, 2005;Winzelberg et al, 2005;Beerens et al, 2013;Missotten et al, 2007;Barca et al, 2011;Wetzels et al, 2010;Mjørud et al, 2014) concluded that cognitive impairment are inversely associated with QoL of elderly people with dementia, except for Monteiro et al (2014) and . These two studies failed to find a statistically significant association between cognitive status and QoL.…”
Section: Physical Factorsmentioning
confidence: 99%
“…Several authors have studied determinants of QoL in older adults (Sloane et al 2005;Hoi et al 2010;Brett et al 2012). A national survey on dependency done in Chile in 2010 showed that QoL in the older individuals is influenced by socio-economic and health-related factors, such as education, number of chronic diseases, self-perceived symptoms of depression and difficulties in activities of daily living (ADL), (SENAMA 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstarted that the light causes a reduction of the symptom called crepuscularism, that is the fact that patients get confused and nervous at sunset. Dr. Philip Sloane and his team have discovered that residents in structures with low levels of light show higher levels of agitation [7]. Exposure to the morning light reduces agitation in patients.…”
Section: Methodsmentioning
confidence: 99%